2010
DOI: 10.1007/s10926-010-9236-6
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Clients’ Perception of Functional Limitations Using the Perceived Functioning & Health Questionnaire

Abstract: Background The Perceived Functioning & Health (PFH) questionnaire was developed to collect, in a standardized manner, which work activities are limited due to health conditions according to the perception of the client. In this study the questionnaire’s reliability and validity are investigated. Methods The PFH questionnaire is comprised of 147 questions, distributed over 33 scales, pertaining to the client’s psychosocial and physical work limitations. The PFH data of 800 respondents were analyzed: 254 healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Claimants could have interest in a certain outcome of a re-assessment. However, IPs are trained in objective assessment of functional limitations; IPs do not mainly focus their assessment on claimants' self-perceived health complaints and impairments but they use many other factors as well [19][20][21].…”
Section: Contextmentioning
confidence: 99%
“…Claimants could have interest in a certain outcome of a re-assessment. However, IPs are trained in objective assessment of functional limitations; IPs do not mainly focus their assessment on claimants' self-perceived health complaints and impairments but they use many other factors as well [19][20][21].…”
Section: Contextmentioning
confidence: 99%
“…While such studies have contributed substantially to the literature and identified the importance of musculoskeletal functioning and mental health as major factors related to work-related disability, there are limitations in utilizing such databases for population research. First, work-related functioning and disability is often assessed in the context of one’s diagnosis and physical health and do not fully capture the impact of the psychosocial domains of disability [49]. Second, in occupational databases, there is often limited individual-level information about important causes, correlates, or consequences of disability such as that which is available from epidemiologic studies.…”
Section: Introductionmentioning
confidence: 99%
“…In such a programme, the focus should not be solely on early signs of complaints, but also on assessing physical work ability and estimating the scope and nature of possible limitations or restrictions in meeting high physical job demands. Information on work ability [9], work limitations [10] or work functioning [11] is often gathered by questionnaires. However, the usefulness of other methods in gathering knowledge on physical work ability should be explored.…”
Section: Introductionmentioning
confidence: 99%